Quantity and quality of retrograde menstruation: a case control study - Drijkoningen Maria; Fülöp Vilmos; Goossens Willy; Bokor Attila; Debrock Sophie; D'Hooghe Thomas (BMC, 2009)
Abstract Background The purpose of this study was to test the hypothesis that menstruation is associated with a higher concentration of endometrial cells in peritoneal fluid(PF) and with increased white and red blood cell concentration in PF when compared to nonmenstrual phases of the cycle. Methods PF was obtained at laparoscopy from 107 women with endometriosis (n = 59) and controls with a normal pelvis (n = 48) during the luteal (n = 46), follicular (n = 38) or menstrual (n = 23) phase of the cycle. Endometriosis was classified according to the classification of the American Society for Reproductive Medicine (rAFS into minimal (n = 25), mild(n = 20), moderate(n = 6) and severe(n = 8) disease. Cell counts (leucocytes, erythrocytes, thrombocytes) were determined on a cell counter. In a subset of 32 patients (13 controls and 19 women with endometriosis), PF was fixed, processed and thinlayers were prepared and stained with Papanicolaou method and with immunocytochemistry using monoclonal antibodies against cytokeratin 7(CK 7), CK 8/18, Ber-Ep4, vimentin, calretinin and CD68. Ber-Ep4 is a marker for cells with epithelial origin (in some cases for mesothelial cells as well). CD68 is specific for cells from monocyte/macrophage lineage; CK7 and CK8/18 are markers for both endometrial epithelial and mesothelial cells, whereas calretinin and vimentin are markers for both endometrial stromal and mesothelial cells. Results In comparison with the nonmenstrual phase of the cycle, analysis of PF during menstruation showed an increased concentration of leucocytes (3.3 × 109/L vs 0.8 × 109/L, P = 0.03), erythrocytes (0.3 × 1012/L vs 0.02 × 1012/L, P = 0.006), hematocrit (0.03 L/L vs 0.003 L/L, P = 0.01) and hemoglobin (0.8 g/dL vs 0.1 g/dL, P = 0.01). Mesothelial cells stained positively with CK7, CK8/18, vimentin, and calretinin. Cells positive for Ber-Ep4 were not observed, except in 2 patients with endometriosis investigated during menses. In all patients 50-98% of single cells were strongly positive for both vimentin and CD68. Conclusion When compared to nonmenstrual phases of the cycle, menstruation is associated with an increased concentration of red and white blood cells in PF. However, the presence of EM cells that are detectable by immunohistochemistry in PF is low during all phases of the cycle, including menstruation.